SPECIFIC FEATURES OF FOREIGN POLICY IN ARAB-MUSLIM STATES: EGYPT AS A CASE STUDY (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article examines the specific features of foreign policy in Arab-Muslim states through the case of the Arab Republic of Egypt. The central argument is that Egyptian foreign policy cannot be explained through a single theoretical lens, whether realism, constructivism, religious identity, or regime-security approaches. Rather, it represents a complex interaction between national security, regime stability, historical self-perception, Arab and Islamic identity, geopolitical position, economic vulnerability, and relations with regional and global powers. Egypt is selected as a case study because it occupies a unique position at the intersection of several geopolitical and civilizational spaces: the Arab world, Africa, the Islamic world, the Mediterranean, the Red Sea, and the wider international system. Its control over the Suez Canal, dependence on the Nile, demographic weight, military-political tradition, and historical claim to regional leadership make Egypt one of the most analytically significant cases for studying Arab-Muslim foreign policy. The article argues that Egypt’s external behavior demonstrates a hybrid model of foreign policy: it combines realist pragmatism, regime-security calculations, Arab-Islamic legitimacy, historical identity, and multi-vector diplomacy. At the same time, Egypt should not be treated as a universal model for all Arab-Muslim states, since its historical experience and geopolitical resources give it a distinct foreign policy profile.
Keywords: Egypt, foreign policy, Arab-Muslim states, Middle East, Arab identity, Islamic factor, regime security, Suez Canal, Nile, multi-vector diplomacy.